Hypertrophic scar management. (2nd March 2023) - Edwards, Jacky
Abstract : Scarring has major psychological and physical repercussions. Scars are often considered trivial, but they can be disfiguring and aesthetically unpleasant and may cause severe itching, tenderness, pain, sleep disturbance, anxiety, depression and disruption of daily activities. It is more efficient to prevent hypertrophic scars than treat them; early diagnosis of a problem scar can considerably impact the overall outcome. Therefore, nurses need to be as knowledgeable about scar products as they are about wound products, and their responsibility should not end once the wound has healed. Appropriate management of the scar will ensure that the wound remains healed and that the patient is happy with the outcome. The nurse is ideally placed to ensure that scars are appropriately identified and treated as early as possible.